The effectiveness of low-frequency electrical stimulation in treating hemiplegic shoulder pain: a systematic review and meta-analysis - Qin, Tao; Hu, Tiantian; Dan, Yuzhuo; Qiu, Cheng; Chen, Mei; Kong, Fanjing; Huang, Sha; Zhai, Zhenwei; Xu, Ying; Sun, Tao (Frontiers in Neurology, 2025)
ObjectiveTo clarify the effectiveness of Low-frequency electrical stimulation (LFES) in treating Hemiplegic shoulder pain (HSP), identify the therapeutic effects of different treatment parameters, and provide evidence-based recommendations.MethodsWe searched PubMed, EMBASE, Web of Science, Cochrane Library, China National Knowledge Infrastructure, Wanfang Data, and China Science and Technology Journal Database up to October 2023. Randomized controlled trials (RCTs) comparing LFES with comparable single rehabilitation interventions, placebo/sham treatments, or conventional rehabilitation were included. The included outcomes were pain intensity and motor function in the upper extremities. The systematic review protocol is available on the International Prospective Register of Systematic Reviews (PROSPERO) (registration number: CRD42023493979).ResultsA total of eight studies (341 participants) were included. LFES showed significant therapeutic effects on shoulder pain scores (SMD = −0.68; 95% CI: [−1.18, −0.18], Z = 2.69, p = 0.006, I2 = 76%). However, the improvement in upper limb motor function (MD = 8.50; 95% CI: [5.12, 11.88], Z = 4.93, p < 0.001, I2 = 16%) was influenced by a single study with lower methodological quality. Subgroup analyses examined factors such as control group type, stimulation type, duration, frequency, pulse width, and stimulation area. The variations in therapeutic effects of LFES across different treatment parameters, different hemiplegic sides, and different stimulation areas were further explored by subgroup analysis.ConclusionThe meta-analysis results indicate that LFES has significant positive effects on alleviating HSP, but its effect on improving motor function requires cautious interpretation due to potential bias.Systematic review registrationInternational Prospective Register of Systematic Reviews (PROSPERO), identifier: CRD42023493979.